Prevalence and Antibiotic Resistance of Bacteria Isolated from Cerebrospinal Fluid of Neurosurgical Patients in Malang, Indonesia - Tommy Alfandy NAZWAR; Bagus Ramanto SAPUTRA; Dewi RETNONINGSIH; Farhad BAL'AFIF; Donny Wisnu WARDHANA (Modern Medicine)
Background: Central nervous system infections are a critical concern in neurosurgical practice, often leading to severe complications and prolonged hospital stays. Understanding the prevalence and antibiotic resistance patterns of the bacteria causing these infections is essential for effective patient management. This study aims to investigate the prevalence and antibiotic resistance profiles of bacteria isolated from cerebrospinal fluid in neurosurgical patients in Malang, Indonesia. Materials and Methods: A retrospective analysis was conducted to investigate the positive cerebrospinal fluid (CSF) cultures in patients who underwent craniotomy within the period of January 2019 to December 2021. The gathered data encompassed the identification of etiological agents and the determination of their respective antimicrobial susceptibilities. Data analysis was performed on a total of 33 individuals, with 67 isolates out of 239 patients and 515 CSF culture samples. Results: The preponderant microorganism identified in the sample was coagulase-negative Staphylococci, with a majority exhibiting methicillin resistance, commonly referred to as methicillin-resistant coagulase-negative Staphylococci (MRCoNS). All specimens exhibited susceptibility to both vancomycin and tigecycline. Klebsiella pneumoniae, a Gram-negative bacterium, was identified as the predominant etiological agent and exhibited resistance to a substantial proportion of the antimicrobial agents tested, specifically 13 out of the 16 antimicrobials evaluated. Conclusions: The sensitivity rates of ceftriaxone and meropenem were found to be 0% and 100%, respectively. The predominant bacteria is MRCoNS, which is completely susceptible to tigecycline, vancomycin, linezolid, and nitrofurantoin. Extended-spectrum beta-lactamase-producing Klebsiella pneumoniae is difficult to treat, especially in central nervous system infections when antimicrobials are scarce.